Electron-impact excitation rate-coefficients and polarization of subsequent emission for Ar+ ion. (June 2016) - Dipti; Srivastava, Rajesh
Abstract: Electron impact excitation in Ar + ions has been studied by using fully relativistic distorted wave theory. Calculations are performed to obtain the excitation cross-sections and rate-coefficients for the transitions from the ground state 3 p 5 ( J =3/2) to fine-structure levels of excited states 3 p 4 4 s, 3 p 4 4 p, 3 p 4 5 s, 3 p 4 5 p, 3 p 4 3 d and 3 p 4 4 d . Polarization of the radiation following the excitation has been calculated using the obtained magnetic sub-level cross-sections. Comparison of the present rate-coefficients is also done with the previously reported theoretical results for some unresolved fine structure transitions. Highlights: Fully relativistic distorted wave theory has been used to study the excitation of fine-structure states of Ar + . We have calculated electron-impact excitation cross-sections for the wide range of incident electron energies. Electron impact excitation rate-coefficients are calculated as a function of electron temperature. Polarization of photons emitted following the decay of the excited fine-structure states are also reported.